Efficient numerical analyses of RC beams subjected to impact loading using axial-flexure-shear fiber beam model. (July 2022) - Wang, W.; Zhou, R.X.; Zhong, J.
Abstract: Similar to wind and seismic loading, impact loading induced by e.g. vessel or vehicle collisions is another type of extreme loading that has become one of the major hazards for the safety of our infrastructural systems such as bridges and buildings. The development of effective strategies which can realistically quantify structural responses under impact loading becomes increasingly important. The widely-used finite-element (FE) simulations using general-purpose FE programs often require excessively high computational cost. This paper therefore aims to develop and implement a computationally efficient axial-flexure-shear fiber beam model based on Timoshenko beam theory with consideration of material non-linearity for the analyses of reinforced concrete (RC) beams under impact loading. The axial, flexural and shear deformation of RC sections during impact are effectively coupled at the fiber and material level. Numerical accuracy of the proposed fiber beam model for non-linear dynamic impact analyses is verified using experimental data from 15 sets of drop-hammer impact tests on scaled RC beams, including flexure-dominant slender beams and shear-dominant deep beams, which demonstrate the great advantage of the proposed fiber beam model over the classical Euler–Bernoulli fiber beam model for applications to impact scenarios where shear deformation of RC members becomes non-negligible.